Nature Finance and Ecosystem Valuation: A Bibliometric Mapping of Financialization of Biodiversity - Judijanto, Loso (Westscience Press, 2025)
This study investigates the evolving landscape of scholarly research on nature finance and the financialization of biodiversity through a comprehensive bibliometric analysis of literature indexed in Scopus from 2000 to 2025. Using VOSviewer, we mapped co-occurring keywords, author networks, temporal trends, and country collaborations to identify dominant themes, emerging topics, and influential contributors. The findings reveal a conceptual transition from traditional ecosystem service valuation toward market-based conservation instruments, including conservation finance, carbon markets, and blockchain-based solutions. The thematic clusters emphasize the increasing intersection between finance, sustainability, and biodiversity policy, with recent trends showing a surge in decentralized finance applications for environmental assets. Notably, the United Kingdom and United States dominate collaborative networks, while Asia-Pacific regions exhibit growing engagement in the field. This study contributes to the theoretical understanding of biodiversity financialization and offers practical insights for policymakers, financial institutions, and environmental stakeholders aiming to design inclusive and effective biodiversity finance strategies. It also identifies gaps for future interdisciplinary research that bridges ecological science with financial innovation.